FINTECH RESEARCH TRENDS: A ANALYSIS OF FINANCIAL TECHNOLOGY - Ulfa Utari; Ryanda Saputra; Rico Syahputra; Melvi Fitri (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The rapid advancement of digital technologies has significantly transformed the global financial sector, giving rise to financial technology (fintech) as a major driver of financial innovation. Fintech integrates advanced technologies such as blockchain, artificial intelligence, and digital platforms to enhance financial services, improve efficiency, and expand financial inclusion. This study aims to analyze the development trends, intellectual structure, and thematic evolution of fintech research through a bibliometric analysis of scientific publications. The data for this study were retrieved from the Scopus database, focusing on fintech-related publications within the selected time period. Bibliometric techniques such as publication trend analysis, citation analysis, co-authorship analysis, keyword co-occurrence analysis, and conceptual structure mapping were employed using bibliometric tools, including Biblioshiny. The results reveal a rapidly expanding fintech research landscape characterized by a significant increase in publications and citations, indicating strong academic interest in the field. The findings also show that countries such as India, China, the United States, and the United Kingdom play dominant roles in fintech research productivity and citation impact. The thematic analysis identifies several key research clusters, including financial inclusion, blockchain technology, digital finance, and artificial intelligence, highlighting the interdisciplinary nature of fintech studies. In addition, network analysis of collaborations indicates increasing international cooperation among researchers and institutions. The study contributes to the existing literature by providing a comprehensive overview of the global fintech research landscape and identifying emerging research directions. The findings offer valuable insights for academics, policymakers, and practitioners in understanding the evolution of fintech research and its implications for the development of digital financial ecosystems